Penerapan Permainan Tradisonal Engklek Untuk Meningkatkan Kemampuan Pramatematika Dan Kemampuan Kemandirian Anak Di TK Negeri Bung Karno Surabaya - Widya Nurkayatin; Ruqoyyah Fitri (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to describe the effectiveness of the implementation of the traditional game "Engklek" in improving pre-mathematics abilities and independence abilities in early childhood at the Bung Karno Surabaya State Kindergarten for the 2023-2024 academic year. This type of research is qualitative descriptive research involving teachers at the Bung Karno State Kindergarten in Surabaya. Data collection was carried out through interview and documentation techniques, then the resulting data was analyzed qualitatively using steps, reduction, display and data verification. The findings from this research show that learning activities at the Bung Karno Surabaya State Kindergarten, through the use of the "Traditional Engklek Game" in order to improve pre-mathematics abilities and independent abilities, can be achieved optimally, so that teaching and learning activities can be carried out by children with a feeling of enjoyment. , without coercion, makes learning more effective. This is shown by the increase in the number of children who are able to count and carry out operations of adding numbers with objects from 1 to 20 independently without guidance from the teacher.